2006
DOI: 10.1074/jbc.m602134200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Properties of Small Heat Shock Protein Hsp25 in MAPK-activated Protein Kinase 2 (MK2)-deficient Cells

Abstract: Small heat shock proteins (sHsps) exist in dynamic oligomeric complexes and display diverse biological functions ranging from chaperone properties to modulator of apoptosis. So far, the role of stress-dependent phosphorylation of mammalian sHsps for its structure and function has been analyzed by using various phosphorylation site mutants overexpressed in different cell types as well as by non-exclusive inhibitors of the p38 MAPK cascade. Here we investigate the role of phosphorylation of endogenous sHsp in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…Additional kinases are also known to regulate HspB1 (reviewed in Ref. 41), and we suspect that these kinases are active developmentally and in adult epidermis. The p38 MAPK pathway resulting in HspB1 phosphorylation is active in keratinocytes subject to stress (31,42).…”
Section: Discussionmentioning
confidence: 99%
“…Additional kinases are also known to regulate HspB1 (reviewed in Ref. 41), and we suspect that these kinases are active developmentally and in adult epidermis. The p38 MAPK pathway resulting in HspB1 phosphorylation is active in keratinocytes subject to stress (31,42).…”
Section: Discussionmentioning
confidence: 99%
“…In human colon cancer cells, however, the p38 activation only leads to a cell-death response when K-Ras gene is mutated, and this selective K-Ras dependent apoptotic effect was shown to be due to a down-regulation of anti-apoptotic vitamin D receptor (VDR) protein expression (94). Knockout studies further revealed a proapoptotic property of the p38 pathway by demonstrating a decreased cell death in cells lacking MKK6 (95), p38alpha (64,96) and MK2 (97). These results together suggest a sufficient role of the p38 pathway in inducing cell death.…”
Section: The Roles Of the P38 Pathway In Regulating Cell Deathmentioning
confidence: 99%
“…Phenylarsine oxide (PAO) was from Sigma-Aldrich. The MK2-inhibitor (2,4-diamino-5H-chromeno-[2,3-b]pyridine-3-carbonitrile; U.S. patent 2004/0127511) was used as described by Vertii et al (Vertii et al, 2006). Poly(vinylidene difluoride) (PVDF) membrane was from PALL (Dreieich, Germany).…”
Section: Suppliersmentioning
confidence: 99%